1976
DOI: 10.1007/bf00277565
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of HS-3, HS-6, benactyzine, and atropine in soman poisoning of dogs

Abstract: Investigations into the therapeutic properties of various combinations of the bispyridinium salts HS-3 and HS-6 and the cholinolytics atropine and benactyzine against soman poisoning in unanesthetized male beagles were performed. In our investigations we observed that: 1. The most effective protection against soman poisoning was attained if both oximes were applied early i.m. 6 min after intoxication together with the cholinolytics. 2. On the basis of clinical symptoms HS-6 proved to have a more intensive ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…It is proposed that benactyzine has more efficiency in preventing somaninduced convulsions in the tested animals. When benactyzine is used, cholinolytic agent is not necessary (46). But our investigation on the effect of benactyzine on human serum BChE showed that benactyzine and drofenine are competitive inhibitors of the enzyme.…”
Section: Anticonvulsant Drugsmentioning
confidence: 83%
“…It is proposed that benactyzine has more efficiency in preventing somaninduced convulsions in the tested animals. When benactyzine is used, cholinolytic agent is not necessary (46). But our investigation on the effect of benactyzine on human serum BChE showed that benactyzine and drofenine are competitive inhibitors of the enzyme.…”
Section: Anticonvulsant Drugsmentioning
confidence: 83%
“…( 1976 ) used atropine plus 100 mg/kg i.v. HS-6 In the treatment of rĩts against soman , while Schenk et al (1976) used a regimen containing 100 mg/kg i.m. HS-6 in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…From the literature , two doses of HS-6 were selected for study to examine some of the cardiovascular effects of HS-6 (Schenk et al, 1976;Wol thuis et al ., 1976). HS-6 or other compounds were injected via the femoral vein and the changes i n soñe cardiovascular and respiratory parameters recorded .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recovery from such poisoning can be achieved by administration of a mixture of muscarinic antagonists and oximes, provided that the phosphoryl-enzyme can be reactivated by the latter. Several organophosphates (such as soman) form a phosphoryl-enzyme adduct which is not reactivated by oximes (4,5), yet the mixture of some oxime/antagonists is still useful in partial protection against saman intoxication (6)(7)(8)(9)(10). This phenomenon led to the idea that oximes may act via the mu'carinic cholinergic receptor, in conjunction with the muscarinic antagonist.…”
Section: Forwardmentioning
confidence: 99%